As percepções da estética queer em fandom de sense8 - COSTA, Edson Júnior Costa da (2024)
This study work aims to study the levels of streaming, from the understanding of queer aesthetics presented on American television available 2015 on the streaming platform Netflix. For this, it carries out a reception study with a group of declared fans of the series. Sense8 production is recognized worldwide for having among its approaches the one that stands out for the LGBTQI+ theme. The theoretical-methodological apparatus of this work is based on conceptual references from the fields of Queer Studies and Cultural Studies of reception in intersection with Cinema and Audiovisual.